The Moderating effect of Innovation Ecosystem on Knowledge Entrepreneurship and Innovation Performance of Manufacturing Firms in Kenya - Isaac Muiruri Gachanja; Stephen Irura Nganga; Lucy Maina Kiganane (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
The turbulent and highly competitive business environment has exposed firms to unprecedented uncertainties brought about by market disruptions. Organizations have attempted to thwart this menace by leveraging on innovation, but innovation activities are complex and are not always viable. The purpose of this study is therefore to examine the moderating effect of Innovation Ecosystem (IE) on the relationship between Knowledge Entrepreneurship (KE) and Innovation Performance (IP) of manufacturing firms in Kenya. The study was anchored on the complexity theory. Mixed method research was applied which utilized cross-sectional design. The target population was 828 manufacturing firms. Purposive and stratified random sampling was used to determine a sample size of 115 firms. The study found that IE has a great moderating effect between KE and IP in manufacturing firms in Kenya. Collaboration and networking between industry, research organizations and universities should be strengthened to promote IP and increase the competitiveness of firms. Further studies should investigate the nature and effects of tension that emanates as a result of knowledge leakage that occurs during interactions with the various players within the IE